Advanced-Country Policies and Emerging-Market Currencies : The Impact of U.S. Tapering on India’s Rupee - Ikeda, Yuki; Medvedev, Denis; Rama, Martin (World Bank Group, Washington, DC, 2015)
The global financial crisis and its aftermath have triggered extraordinary policy responses in advanced countries. The impacts of these policy responses—from asset price bubbles to currency depreciations—have often been felt in the developing world. As tapering talk evolves into actual withdrawal of quantitative easing in the United States, and as the Euro Zone launches its own quantitative easing program, there are good reasons to be concerned about the financial stability of emerging economies. India's experience with U.S. tapering offers insights into what to expect. This paper estimates the contribution of external and domestic factors to short-term fluctuations in the value of the Indian rupee between 2004 and 2014, using a rich dynamic model that controls for a large number of exchange rate determinants. The paper finds that a global surprise factor, more than domestic vulnerabilities, was the main driver of the large rupee depreciation in summer 2013. With the surprise factor gone, further normalization of U.S. monetary policy is unlikely to have significant effects on the rupee exchange rate.